Impact of sensory-based food education in kindergarten on willingness to eat vegetables and berries - Ulla Hoppu; Mira Prinz; Pauliina Ojansivu; Oskar Laaksonen; Mari A. Sandell (Food & Nutrition Research, 2015)
Background: Children use all of their senses when exploring new foods, and sensory-based food education provides new possibilities for promoting healthy dietary habits. Objective: To evaluate the effect of sensory-based food education activities on children's willingness to eat test samples of selected vegetables and berries. Design: Two kindergartens in Hanko, Finland, participated in the study and the subjects were children aged 3–6 years, divided in the intervention (n=44) and control (n=24) kindergarten. In the intervention kindergarten, five sensory-based food education sessions focusing on vegetables and berries were implemented, once per week for 5 weeks. A tasting protocol was performed with the children at baseline and after the intervention. The willingness to eat (5 different vegetables and 3 Finnish berries) was categorised. Parents also filled in a questionnaire on the children's food preferences at home. Results: In the intervention kindergarten, the willingness to eat the samples increased significantly (p≤0.001, Wilcoxon and Friedman), while in the control kindergarten, no significant change was observed when all of the test samples were taken into account. The parental report of their children's preferences and children's actual eating of the test samples corresponded relatively weakly. Conclusions: Sensory-based food education activities may promote a willingness to eat vegetables and berries. Child-centred test methods are important for evaluating the effects of dietary interventions among children.